(untitled) - Bible. English. New International. 1994.; Bible. English. New Revised Standard. 1994. (Nashville, TN Abingdon, 2002)
Contents: v.10 : The Acts of the Apostles, Introduction to epistolary literature, The letter to the Romans, The first letter to the Corinthians. Includes bibliographical references, maps, charts, etc.
Full texts and critical notes of the New International Version and New Revised Standard Version of the Bible in parallal columns.
Keywords: Abingdon press; Bible -- commentaries